Cognitive apprenticeship in clinical practice: can it stimulate learning in the opinion of students? - Stalmeijer, Renée E. (Springer Netherlands, 2008)
Learning in clinical practice can be characterised as situated learning because students learn by performing tasks and solving problems in an environment that reflects the multiple ways in which their knowledge will be put to use in their future professional practice. Collins et al. introduced cognitive apprenticeship as an instructional model for situated learning comprising six teaching methods to support learning: modelling, coaching, scaffolding, articulation, reflection and exploration. Another factor that is looked upon as conducive to learning in clinical practice is a positive learning climate. We explored students’ experiences regarding the learning climate and whether the cognitive apprenticeship model fits students’ experiences during clinical training. In focus group interviews, three groups of 6th-year medical students (N = 21) discussed vignettes representing the six teaching methods and the learning climate to explore the perceived occurrence of the teaching methods, related problems and possibilities for improvement. The students had experienced all six teaching methods during their clerkships. Modelling, coaching, and articulation were predominant, while scaffolding, reflection, and exploration were mainly experienced during longer clerkships and with one clinical teacher. The main problem was variability in usage of the methods, which was attributed to teachers’ lack of time and formal training. The students proposed several ways to improve the application of the teaching methods. The results suggest that the cognitive apprenticeship model is a useful model for teaching strategies in undergraduate clinical training and a valuable basis for evaluation, feedback, self-assessment and faculty development of clinical teachers.